Coronary CTA-specific Definitions of High-Risk Plaque Features Improve Detection of ACS: Results from the ROMICAT II Trial - Bittner, Daniel O. (Circ Cardiovasc Imaging, 2018)
BACKGROUND: High-risk plaque features (HRP) as detected by coronary CT angiography (CTA) predict acute coronary syndrome (ACS). We sought to determine whether coronary CTA-specific definitions of HRP improve discrimination of patients with ACS as compared to definitions from intravascular ultrasound (IVUS). METHODS AND RESULTS: In patients with suspected ACS, randomized to coronary CTA in the ROMICAT II trial, we retrospectively performed semi-automated quantitative analysis of HRP (including remodeling index, plaque burden as derived by plaque area, low CT attenuation plaque volume) and degree of luminal stenosis and analyzed the performance of traditional IVUS thresholds to detect ACS. Further, we derived CTA-specific thresholds in ACS patients to detect culprit lesions, and applied those to all patients to calculate the discriminatory ability to detect ACS in comparison to IVUS thresholds. Out of 472 patients, 255 patients (56±7.8 years; 63% men) had coronary plaque. In 32 patients (6.8%) with ACS, culprit plaques (n=35) differed from non-culprit plaques (n=172) with significantly greater values for all HRP features except minimal luminal area (significantly lower) (all p<0.01). IVUS definitions showed good performance while minimal luminal area (OR: 6.82; p=0.014) and plaque burden (OR: 5.71, p=0.008) were independently associated with ACS, but not remodeling index (OR: 0.78; p=0.673). Optimized CTA-specific thresholds for plaque burden (AUC: 0.832 vs. 0.676) and degree of stenosis (AUC: 0.826 vs. 0.721) showed significantly higher diagnostic performance for ACS as compared to IVUS based thresholds (all p<0.05) with borderline significance for minimal luminal area (AUC: 0.817 vs. 0.742; p=0.066). CONCLUSIONS: CTA-specific definitions of high-risk plaque features may improve the discrimination of patients with ACS as compared to IVUS based definitions.